Turkey prostate cancer map 2021: Turkish urooncology association prostate cancer database report - ŞAHİN, BAHADIR; TİNAY, İLKER (My University, 2022)
Objective: This study aimed to present the data of patients with prostate cancer (PCa) whose detailed information was stored in the Urologic Cancer DatabaseProstate, Urooncology Association, Turkey with the title of “Turkey Prostate Cancer Map 2021.” Materials and Methods: Patient data between 1995 and 2020 were retrospectively scanned. The age of the patients, their distribution according to age groups, symptoms during diagnosis, examination findings [digital rectal examination (DRE)], prostate-specific antigen (PSA) values, biopsy methods in the diagnosis, metastatic disease rates, treatment methods, and progression rates at follow-up were examined. These results were compared with the results of the previous report, namely “Prostate Cancer Incidence (Incidence) in Turkey,” by the Urooncology Association in Turkey in 2009. Results: This study analyzed the data of 5040 patients from 19 different centers. The mean patient age was 63.6 (37-97) years. The age distribution examination revealed that most patients (49.8%) were aged 60-69 years. Of the patients, 51.8% were symptomatic at the time of diagnosis. The presence of symptoms was determined in 88.6% in 2009 data. The DRE of patients revealed that 25% of patients had malignancy findings. The PSA distribution examination revealed a >10 ng/mL PSA value in 37.5% of patients. With the increasing use of magnetic imaging resonance (MRI) in PCa diagnosis over the years, increased MR-fusion biopsy rates have been observed. Considering the biopsy data, 91% of patients were diagnosed with a classical transrectal ultrasound-guided biopsy, whereas 9% were diagnosed with MR-Fusion biopsy. Fusion biopsies revealed that 23% of patients with Prostate Imaging-Reporting and Data System (PI-RADS) 4 lesion and 57% with PI-RADS 5 lesion were diagnosed with cancer. Of the patients, 8.9% of patients had metastases during the initial diagnosis. This rate was 17% in 2009 data. The treatment methods examination after the diagnosis revealed that 73.9% of patients had undergone radical prostatectomy. This rate was 51.8% in 2009. Robotic and laparoscopic approaches, which are among the surgical modalities, have increased over the years. However, the most frequently applied modality in our country was open radical prostatectomy with 62.6%. Considering the follow-up data after treatment, 8.9% of patients had progression, of which 62.6% was biochemical, 30.2% was radiological, and 6.9% was a clinical progression. Conclusion: Technological advancements for PCa diagnosis (MRI and MR-guided biopsies) are becoming a routine part of daily practice compared to the results of the “Prostate Cancer Incidence in Turkey” project in 2009. The comparative study results revealed that the rate of symptomatic and metastatic disease decreases at the time of diagnosis, and laparoscopic and robotic surgery methods are used at increasing rates for localized disease
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Oncology; Health Sciences; ONKOLOJİ; Klinik Tıp; Klinik Tıp (MED); ONCOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Epidemiology; prostate; prostate biopsy; prostate cancer; RADICAL PROSTATECTOMY; RISK; Epidemiology; prostate; prostate biopsy; prostate cancer